1961
DOI: 10.1182/blood.v18.4.431.431
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Sequential and Combination Antimetabolite Therapy in Acute Leukemia: 6-Mercaptopurine and Methotrexate

Abstract: The efficacy of three therapeutic programs for acute leukemia were compared. These programs included (1) Methotrexate (Phase I) followed by 6-mercaptopurine (Phase II); (2) 6-mercaptopurine (Phase I) followed by Methotrexate (Phase II); and (3) Combination Therapy, i.e., 6-mercaptopurine given in combination with Methotrexate. In children with acute lymphocytic leukemia the remission rate was 59 per cent for combination therapy, 47 per cent for 6-mercaptopurine, and 29 per cent for Methotrexate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
3

Year Published

1963
1963
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(77 citation statements)
references
References 14 publications
4
70
0
3
Order By: Relevance
“…Whether methotrexate would decrease thiopurine metabolite concentrations in leukemic blasts after highdose intravenous or conventional-dose oral mercaptopurine during continuation therapy (when there is not the more substantial leukemia burden that is present in newly diagnosed cases) is not known. However, there are circumstantial data that methotrexate and mercaptopurine may synergize (or at least avoid antagonism) when combined during continuation therapy; there is a long track record of methotrexate and low-dose oral mercaptopurine having been successfully combined, 34,35 and erythrocyte thioguanine nucleotides correlate with the active metabolites of methotrexate during continuation therapy with methotrexate plus lowdose oral mercaptopurine. 13 Thus it is possible that methotrexate synergizes with low-dose oral mercaptopurine during continuation therapy, a time at which too few blast cells exist in vivo to be readily detected with current techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Whether methotrexate would decrease thiopurine metabolite concentrations in leukemic blasts after highdose intravenous or conventional-dose oral mercaptopurine during continuation therapy (when there is not the more substantial leukemia burden that is present in newly diagnosed cases) is not known. However, there are circumstantial data that methotrexate and mercaptopurine may synergize (or at least avoid antagonism) when combined during continuation therapy; there is a long track record of methotrexate and low-dose oral mercaptopurine having been successfully combined, 34,35 and erythrocyte thioguanine nucleotides correlate with the active metabolites of methotrexate during continuation therapy with methotrexate plus lowdose oral mercaptopurine. 13 Thus it is possible that methotrexate synergizes with low-dose oral mercaptopurine during continuation therapy, a time at which too few blast cells exist in vivo to be readily detected with current techniques.…”
Section: Discussionmentioning
confidence: 99%
“…T h e consortium of investigative research No. 6 ALL OF CHILDHOODcenter and collaborating physicians should provide patients with advances in therapy at the earliest possible time, and provide a medium for continuing education.…”
Section: Cancer Decementioning
confidence: 99%
“…Residual tumor size after chemotherapy was estimated by comparing the slope of repopulation (the time to death) with the behavior of control animals with known numbers of injected cells.19 In patients, too, this approach has been of major importance in estimating residual tumor size after chemotherapy. T h e slope of repopulation was determined by serial determinations in the patient himself, where the endpoint was not death but reappearance of leukemia in the marrow (at which time the child was treated with additional chemotherapy).ll Thus, programs of intensive chemotherapy have been undertaken which inclrided deliberate cessa- No. 6 ALL OF CHILDHOODtion of drug administration to determine the effects of the treatment administered.llJ2 This strategy has been reckoned as ethically acceptable since survival experience was not inferior to contemporaneous programs of management involving maintenance chemotherapy.13 T h e long range strategy has been to define the impact of various therapeutic procedures, the better to combine them eventually.…”
mentioning
confidence: 99%
“…Following the initial report of the effectiveness of folic acid antagonists in the remission induction of ALL [9], subsequent studies with low doses of methotrexate (1-5 mg) have demonstrated a complete remission rate of 20% to 30% in previously untreated children [ 1,21 . Somewhat higher doses of methotrexate (1 -5 mg/kg) have resulted in complete remissions in children previously treated with methotrexate [ 10-121.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate is known to be an active agent in the treatment of acute lymphocytic leukemia (ALL) [ 1,2] . Although it is not currently used alone for the remission induction of patients with ALL, methotrexate is frequently included in maintenance chemotherapy programs or administered intrathecally as central nervous systems (CNS) prophylaxis.…”
Section: Introductionmentioning
confidence: 99%